2013
DOI: 10.1002/j.1681-4835.2013.tb00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing The Usage Of The Tribal Land Information Management System For Land Management And Administration: The Case Of Mogoditshane Subordinate Land‐Board

Abstract: Land Information Systems are touted to be critical for efficient land management and administration. If properly used and updated, they can inform decision makers in a timely fashion on land resources utilisation. The Government of Botswana has consequently implemented a Tribal Land Information Management System (TLIMS) at Mogoditshane SubLand Board. This study seeks to evaluate the extent to which the TLIMS meets its intended purpose of improving land management and administration. The study also tries to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In the Botswana context, the issues of behaviour and attitudes towards records are not clearly defined and can only be gleaned and inferred from previous studies. In Botswana, studies done by Mooketsi and Leonard (2013); Bwalya et al (2015); Mosweu, Bwalya and Mutshewa (2016) report non-use of information systems, lack of user guidelines, information technology infrastructure, training on the system, user resistance and information preferences in the organisation they studied. These studies conducted in Botswana focused on user behaviour and the level of acceptance of electronic records.…”
Section: Attitudes and Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Botswana context, the issues of behaviour and attitudes towards records are not clearly defined and can only be gleaned and inferred from previous studies. In Botswana, studies done by Mooketsi and Leonard (2013); Bwalya et al (2015); Mosweu, Bwalya and Mutshewa (2016) report non-use of information systems, lack of user guidelines, information technology infrastructure, training on the system, user resistance and information preferences in the organisation they studied. These studies conducted in Botswana focused on user behaviour and the level of acceptance of electronic records.…”
Section: Attitudes and Behaviourmentioning
confidence: 99%
“…In contrast, the records system was fully utilised in municipalities that expressed trust in the system. Furthermore, Mooketsi and Leonard (2013) found that in Lands Boards, employees in Botswana found the records system disappointing and frustrating; therefore, there was low usage of this system, which means few records were captured or even not captured at all in the system.…”
Section: Figure 3: Use Of the Records System (N=101)mentioning
confidence: 99%
“…Hence, many countries have developed an LIS to assist them in managing their land more effectively [17]. Indonesia adopted an LIS in 1997 to support its land management.…”
Section: Introductionmentioning
confidence: 99%